PREPARATION, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITIES OF SOME TRANSITION METAL COMPLEXES WITH 4-HYDROXYPYRIDINE AND NITRITE ION - JEEVA ,J.; RAMACHANDRAMOORTHY, T. (International Journal of Pharma and Bio Sciences, 2013)
By the irradiation of microwave, transition metal complexes of zinc, cadmium and mercury were prepared with the ligands 4–hydroxypyridine (4-HP) and Nitrite ion (NO2)- .These complexes were studied for metal estimation, electrical conductance, CHN analysis, IR, electronic and NMR spectra. All the synthesized complexes were studied and screened for antibacterial and antifungal activities in detail.